In situ fabrication of a 2D Ni2P/red phosphorus heterojunction for efficient photocatalytic H2 evolution. (July 2019) - Liu, Enzhou; Qi, Lulu; Chen, Jibing; Fan, Jun; Hu, Xiaoyun
Graphical abstract: Highlights: Ni2 P/red phosphorus heterojunction was fabricated by a simple in situ hydrothermal strategy. Ni2 P/red phosphorus with 2D nanostructure has good contact interface and stability. The surface edge of red phosphorus is the active sites during the photocatalytic reaction. Ni2 P as co-catalyst can induce more active sites and improve the charge separation. Ni2 P can greatly enhance the photocatalytic H2 production efficiency of red phosphorus. Abstract: Highly available and active photocatalysts and cocatalysts play key roles in the of efficient and stable visible-light-driven photocatalytic systems. In this work, a nickel phosphide (Ni2 P)/red phosphorus (RP) heterojunction composite was fabricated for the first time by an in situ hydrothermal method using nanosized RP and nickel chloride as the starting materials. The results indicated that the heterojunction exhibits a two-dimensional (2D) nanostructure with a good contact interface and stability. The surface edges of pure RP are the active sites during the photocatalytic reaction. The introduction of Ni2 P could improve the light-harvetsing ability of RP and facilitate charge separation, leading to an enhanced photocurrent intensity and excellent photocatalytic performance for H2 evolution. The H2 production rate of the 3% Ni2 P/RP sample was 2183 μmol·g −1 ·h −1 under visible light irradiation, which was higher than that of Pt/RP, indicating that Ni2 P could be used as an efficient noble-metal-free cocatalyst. In addition, a possible mechanism for H2 production was proposed for Ni2 P/RP composite. Further work should be conducted in the exploration of P-based transition metal cocatalysts and RP-based photocatalysts.